Behavioral, Virologic, and Immunologic Factors Associated With Acquisition and Severity of Primary Epstein-Barr Virus Infection in University Students - Balfour, Henry H.; Odumade, Oludare A.; Schmeling, David O.; Mullan, Beth D.; Ed, Julie A.; Knight, Jennifer A.; Vezina, Heather E.; Thomas, William; Hogquist, Kristin A. (The Journal of infectious diseases, 2013)
Background. University students were studied prospectively to determine the incidence of and risk factors for acquisition of primary Epstein-Barr virus (EBV) infection and the virologic and immune correlates of disease severity. Methods. EBV antibody-negative freshmen participated in monthly surveillance until graduation. If antibodies developed, proximate samples were assayed for viral load by polymerase chain reaction. Lymphocyte and natural killer (NK) cell numbers and activation were measured by flow cytometry, and plasma cytokine levels were measured by a multiplex assay. Results. Of 546 students screened, 202 (37%) were antibody negative; 143 antibody-negative students were enrolled. During a median of 3 years of observation, 66 subjects experienced primary infection. Of these, 77% had infectious mononucleosis, 12% had atypical symptoms, and 11% were asymptomatic. Subjects reporting deep kissing with or without coitus had the same higher risk of infection than those reporting no kissing (< .01). Viremia was transient, but median oral shedding was 175 days. Increases were observed in numbers of NK cells and CD8⁺ T-cells but not in numbers of CD4⁺ T-cells during acute infection. Severity of illness correlated positively with both blood EBV load (P = .015) and CD8⁺ lymphocytosis (P = .0003). Conclusions. Kissing was a significant risk for primary EBV infection. A total of 89% of infections were symptomatic, and blood viral load and CD8⁺ lymphocytosis correlated with disease severity.